EVALUATION THE EFFECT OF GREEN SYNTHESIS TITANIUM DIOXIDE NANOPARTICLES ON ACINETOBACTER BAUMANNII ISOLATES - & Yaaqoob, Hamza (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Acinetobacter baumannii is gram negative opportunistic coccobacilli,the most important agent in nosocomial infections with high mortality rate. This bacteria is characterized by (biochemical tests, polymerase chain reaction (PCR) and vitek-2 system). The antibiotic susceptibility result of A. baumannii isolates were shown resistant to (Methicillin, Nitrofurantion), while sensitive to (colistin, Ciprofloxacin).This study was aimed to biosynthesis of titanium dioxide nanoparticles by using prodigiosin pigment produced from clinical isolate Serratia marcescens as reducing and stabilizing agent for Titanium dioxide nanoparticles (TiO2 NPs) and used as antibacterial agent for Acinetobacter baumannii isolated from different clinical sources. TiO2 NPs synthesized by using titanium chloride TiCl4 (5 ml/50 ml) in deionized water with concentration of prodigiosin (10 mg/ml)and adjusted pH at 7 and the temperature at 50 ˚C. TiO2NPs synthesized was Characterized by various technique, such as (AFM , UV-VIS, FTIR , XRD and FE-SEM ). The result showed that wavelength(366)nm was optimum for TiO2NPs that have crystalline shape at average volume (47.52 nm). Green synthesized TiO2 NPs have shown several applications such as biomedical, anticancer, bio sensing, catalysis etc.